Secondary matrix-associated autologous chondrocyte implantation after failed cartilage repair shows superior results when combined with autologous bone grafting: findings from the German Cartilage Registry (KnorpelRegister DGOU) - Weishorn, Johannes; Niemeyer, Philipp; Angele, Peter; Spahn, Gunter; Tischer, Thomas; Renkawitz, Tobias; Bangert, Yannic (Knee surgery, sports traumatology, arthroscopy, 2024)
Purpose The aim of this study was to evaluate whether additive autologous bone grafting (ABG) improves clinical outcome and survival in revision matrix-associated autologous chondrocyte implantation (M-ACI) after failed cartilage repair (CR). Methods A retrospective, registry-based, matched-pair analysis was performed to compare patient-reported outcomes and survival in secondary M-ACI with or without additional bone grafting for focal full-thickness cartilage defects of the knee and to compare it with those in primary M-ACI. Patients were matched for age, sex, body mass index, defect size and localization, and number of previous CRs. The Knee Injury and Osteoarthritis Outcome Score (KOOS) was assessed over a follow-up period of 36 months. The patient acceptable symptomatic state, the clinical response rate and the survival of the subgroups were determined. Results A total of 818 patients were matched. Revision M-ACI (n = 238) with concomitant bone grafting was associated with significantly higher PRO as measured by KOOS (80.8 ± 16.8 vs. 72.0 ± 17.5, p = 0.032) and higher CRR (81.4% vs. 52.0%, p = 0.018) at 36 months compared to patients with revision M-ACI alone. KOOS and KOOS improvement in these patients did not differ from those who underwent primary M-ACI (p = n.s.). The combination of M-ACI and ABG resulted in a significantly higher KOOS at 36 months than M-ACI alone, regardless of whether bone marrow stimulation (89.6 ± 12.5 vs. 68.1 ± 17.9, p = 0.003) or ACI (82.6 ± 17.0 vs. 72.8 ± 16.0, p = 0.021) was performed before. Additional bone grafting results in equivalent survival rates at 7 years in secondary compared to primary M-ACI (83% vs. 84%, p = n.s.). Conclusions Regardless of the type of previous CR, additional bone grafting in secondary M-ACI improves the clinical outcome, response rate and survival at 36 months compared to M-ACI alone. Secondary M-ACI with ABG had comparable clinical response and survival rates to primary M-ACI. Therefore, subchondral bone should be treated even in cases of mild bone involvement in revision M-ACI. Level of evidence Level III.
Gesehen am 05.03.2025